Incidence of kampo medicine‐induced interstitial pneumonia: 10 year retrospective study at a university hospital kampo medicine department. Issue 1 (18th February 2019) - Nogami, Tatsuya; Fujimoto, Makoto; Shimada, Yutaka; Watari, Hidetoshi; Kitahara, Hideyuki; Kimbara, Yoshiyuki; Nakagawa, Hajime; Shibahara, Naotoshi
ABSTRACT: Aim: At present, traditional Japanese medicines, termed kampo medicines, are integrated into the Japanese national health‐care system. In Japan, interstitial pneumonia is described as an adverse drug event in the drug package insert of some prescription kampo formulations. Additionally, many of the kampo formulas that induce interstitial pneumonia contain Scutellariae Radix (SR). The incidence of kampo medicine‐induced interstitial pneumonia has not been sufficiently studied. The aim of the present study was therefore to assess the incidence of kampo medicine‐induced interstitial pneumonia in the kampo medicine department of a clinical institution. Methods: We selected patients who had developed interstitial pneumonia due to kampo formulas on the basis of the medical records of the Department of Japanese Oriental Medicine, Toyama University Hospital, from 2008 to 2017. Moreover, we investigated the number of patients who were prescribed kampo formulas and the number of patients who were prescribed kampo formulas containing SR during the study period. Results: Of the 3590 patients who received kampo medications in the 10 year survey period, three patients developed kampo medicine‐induced interstitial pneumonia (incidence, 0.08%). The causal kampo formulas in all three of these cases contained SR. For the 1111 patients who were prescribed SR‐containing formulas, the incidence of kampo medicine‐induced interstitial pneumonia was 0.27%. Conclusion: Although the incidence is not high, physicians should keep in mind that kampo formulas, particularly SR‐containing formulas, might cause kampo medicine‐induced interstitial pneumonia.